2022
DOI: 10.3389/fendo.2022.954730
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin-2 is associated with FGF23 in WNT1 and PLS3 osteoporosis

Abstract: BackgroundThe pathogenic mechanisms of early-onset osteoporosis caused by WNT1 and PLS3 mutations are incompletely understood and diagnostic biomarkers of these disorders are limited. Recently, lipocalin-2 has been recognized as an osteokine involved in bone development and homeostasis. However, the role of lipocalin-2 in WNT1 and PLS3 osteoporosis is unknown.ObjectiveWe aimed to investigate if plasma lipocalin-2 could be utilized as a biomarker for WNT1 and PLS3 osteoporosis and to evaluate the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Recently, a Finnish group found that lipocalin-2 is associated with FGF23 in 14 osteoporotic patients with PLS3 pathogenic vairants. Although comparison was made for FGF23 levels between in PLS3 patients and healthy subjects (66). DKK1, sclerostin, an inhibitor of the WNT signaling pathway, and FGF23 are primarily secreted by the osteocytes (67,68).…”
Section: Calcium Regulation In Osteocytesmentioning
confidence: 99%
“…Recently, a Finnish group found that lipocalin-2 is associated with FGF23 in 14 osteoporotic patients with PLS3 pathogenic vairants. Although comparison was made for FGF23 levels between in PLS3 patients and healthy subjects (66). DKK1, sclerostin, an inhibitor of the WNT signaling pathway, and FGF23 are primarily secreted by the osteocytes (67,68).…”
Section: Calcium Regulation In Osteocytesmentioning
confidence: 99%